Dominant efficiency of nonregular patterns of subthalamic nucleus deep brain stimulation for Parkinson's disease and obsessive-compulsive disorder in a data-driven computational model. (21st December 2015) - Karamintziou, Sofia D; Deligiannis, Nick G; Piallat, Brigitte; Polosan, Mircea; Chabardès, Stephan; David, Olivier; Stathis, Pantelis G; Tagaris, George A; Boviatsis, Efstathios J; Sakas, Damianos E; Polychronaki, Georgia E; Tsirogiannis, George L; et al.
Abstract: Objective. Almost 30 years after the start of the modern era of deep brain stimulation (DBS), the subthalamic nucleus (STN) still constitutes a standard stimulation target for advanced Parkinson's disease (PD), but the use of STN-DBS is also now supported by level I clinical evidence for treatment-refractory obsessive-compulsive disorder (OCD). Disruption of neural synchronization in the STN has been suggested as one of the possible mechanisms of action of standard and alternative patterns of STN-DBS at a local level. Meanwhile, recent experimental and computational modeling evidence has signified the efficiency of alternative patterns of stimulation; however, no indications exist for treatment-refractory OCD. Here, we comparatively simulate the desynchronizing effect of standard (regular at 130 Hz) versus temporally alternative (in terms of frequency, temporal variability and the existence of bursts or pauses) patterns of STN-DBS for PD and OCD, by means of a stochastic dynamical model and two microelectrode recording (MER) datasets. Approach. The stochastic model is fitted to subthalamic MERs acquired during eight surgical interventions for PD and eight surgical interventions for OCD. For each dynamical system simulated, we comparatively assess the invariant density (steady-state phase distribution) as a measure inversely related to the desynchronizing effect yielded by the applied patterns of stimulation. Main results. We demonstrate that high (130 Hz)—and low (80 Hz)—frequency irregular patterns of stimulation, and low-frequency periodic stimulation interrupted by bursts of pulses, yield in both pathologic conditions a significantly stronger desynchronizing effect compared with standard STN-DBS, and distinct alternative patterns of stimulation. In PD, values of the invariant density measure are proven to be optimal at the dorsolateral oscillatory region of the STN including sites with the optimal therapeutic window. Significance. In addition to providing novel insights into the efficiency of low-frequency nonregular patterns of STN-DBS for advanced PD and treatment-refractory OCD, this work points to a possible correlation of a model-based outcome measure with clinical effectiveness of stimulation and may have significant implications for an energy- and therapeutically-efficient configuration of a closed-loop neuromodulation system.